2002
DOI: 10.1097/00005768-200202000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and the presence and extent of calcified coronary atherosclerosis

Abstract: Physical activity, particularly high-intensity exercise in sports-related activities, promotes a healthy cardiovascular risk profile, including lower body mass index and insulin resistance, but is unrelated to coronary calcification. This suggests that the risk reduction associated with physical activity is mediated by factors other than retarding the development of calcified atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 33 publications
4
33
2
1
Order By: Relevance
“…Therefore this finding is also consistent in direction with several clinical trials including the Heidelberg Regression Study [22,23], the Stanford Coronary Risk Intervention Project [24], and the Lifestyle Heart Trial [25,26], in which coronary artery disease (CAD) patients who had exercise training with a low-fat diet [22,23] or exercise training with other lifestyle modification (stop smoking, low-fat diet, and stress management) [24][25][26] had a slower progression of coronary atherosclerosis, as compared with control patients with CAD. In contrast, our findings indicate that there is no association between baseline physical activity and CAC, consistent with reports from the US Army Personnel Study and the Atherosclerosis Risk in Communities (ARIC) Study both of which showed no association between physical activity and CAC [19,20]. This may be due to imprecise measurement of physical activity in both observational and cross-sectional studies, which may have underestimated the true odds ratios.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Therefore this finding is also consistent in direction with several clinical trials including the Heidelberg Regression Study [22,23], the Stanford Coronary Risk Intervention Project [24], and the Lifestyle Heart Trial [25,26], in which coronary artery disease (CAD) patients who had exercise training with a low-fat diet [22,23] or exercise training with other lifestyle modification (stop smoking, low-fat diet, and stress management) [24][25][26] had a slower progression of coronary atherosclerosis, as compared with control patients with CAD. In contrast, our findings indicate that there is no association between baseline physical activity and CAC, consistent with reports from the US Army Personnel Study and the Atherosclerosis Risk in Communities (ARIC) Study both of which showed no association between physical activity and CAC [19,20]. This may be due to imprecise measurement of physical activity in both observational and cross-sectional studies, which may have underestimated the true odds ratios.…”
Section: Discussionsupporting
confidence: 85%
“…An inverse association between cardiorespiratory fitness and carotid artery intima-media thickness has been reported [17,18]. Although no association was seen between coronary calcium scores and physical activity [19,20], a close correlate of fitness [21], several clinical trials have also shown that exercise training coupled with other lifestyle modifications slowed progression of coronary atherosclerosis in CHD patients [22][23][24][25][26]. To address atherosclerotic vascular disease prevention strategies, it is important to investigate whether cardiorespiratory fitness is associated with reduced early atherosclerotic vascular disease risk in young adults.…”
Section: Introductionmentioning
confidence: 98%
“…Desai et al 30 found long duration physical activity to be inversely related to CAC independent of other confounding variables. On the contrary, Taylor et al 31 found no significant relationship between physical activity, particularly high-intensity physical activity and the extent of CAC.…”
Section: Discussionmentioning
confidence: 92%
“…Various studies have examined associations between physical activity and markers of subclinical atherosclerosis, although the data are equivocal. [11][12][13][14][15][16][17][18][19] These inconsistencies may in part be due to differences in the assessment of physical activity and limitations imposed by self-reported data. In the only study to date to have used an objective assessment of physical activity, there was an inverse association between vigorous activity and 3-year progression in common carotid artery intima media thickness.…”
mentioning
confidence: 99%